Business intelligence numa consultora de seguros : um projeto de reformulação e implementação - Gonçalves, Leandro Magalhães (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence